The Potential of Hormonal Contraception to Influence Female Sexuality - de Castro Coelho, Filipa; Barros, Cremilda (International Journal of Reproductive Medicine, 2019)
The association between female sexual function and hormonal contraception is controversial. Recognition and management of sexual side effects in women using hormonal contraceptives are challenging. An unsatisfactory number of studies report the influence of the available contraceptives on female sexuality. This article provides an updated narrative review regarding the effect and the magnitude of the impact that hormonal contraceptives play in female sexual function.